2009
DOI: 10.1038/labinvest.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

A possible suppressive role of galectin-3 in upregulated osteoclastogenesis accompanying adjuvant-induced arthritis in rats

Abstract: Galectin-3 is a b-galactoside-binding animal lectin having pleiotropic effects on cell growth, differentiation, and apoptosis. This lectin has been shown to be involved in phagocytosis by macrophages and in inflammation. Here we investigated an involvement of galectin-3 in the regulatory process of inflammatory bone resorption in rats with adjuvant-induced arthritis (AA rats) accompanying severe bone destruction in the ankle joints. The protein level of galectin-3 in the ankle-joint extracts was markedly augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…22 Five-week-old female Lewis rats were anesthetized with diethyl ether and were intradermally injected at the base of the tail with complete Freund adjuvant (CFA) containing 25 mg/kg heat-killed M. butyricum (Difco Laboratories) suspended in mineral oil. For the control experiments, rat were injected with mineral oil alone.…”
Section: Osteoclast Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Five-week-old female Lewis rats were anesthetized with diethyl ether and were intradermally injected at the base of the tail with complete Freund adjuvant (CFA) containing 25 mg/kg heat-killed M. butyricum (Difco Laboratories) suspended in mineral oil. For the control experiments, rat were injected with mineral oil alone.…”
Section: Osteoclast Differentiationmentioning
confidence: 99%
“…22 The total proteins were extracted in the lysis buffer containing 1% Triton X-100, 0.5% NP-40, 150 mM NaCl, 50 mM Tris-HCl (pH 7.4), 1 mM NaF, 1 mM Na 3 VO 4 , 1 mM phenylmethylsulfonyl fluoride, and protease inhibitor cocktail (Sigma, St Louis, MO, USA). Cell lysates, containing equal amounts of proteins, were subjected to 10% SDS-PAGE and transferred to nitrocellulose membranes.…”
Section: Western Blottingmentioning
confidence: 99%
“…26,27 Interestingly, Chen et al 28 demonstrated AP-1 and NF-κB inhibition by citrus pectin in activated macrophages, but this effect was associated with the suppression of LPS/TLR-4 signaling. On the other hand, galectin-3 did not affect signaling through NF-κB in macrophages, 29 whereas galectin-3 activated NF-κB in colonic epithelial lamina propria fibroblasts and rheumatoid arthritis synovial fibroblasts. 30,31 Since nuclear phosphorylated galectin-3 also interacts with other transcription factors (eg, AP-1, TTF-1, SP1, and CRE) and controls the expression of cancer-related genes, 32 it is possible that MCP inhibits the interactions between galectin-3 and NF-κB or AP-1, which results in the inhibition of the expression and secretion of uPA.…”
Section: Discussionmentioning
confidence: 84%
“…13) In addition, sugar-binding proteins such as siglec, which interact with sialic acid, and galectins, which interact with Galβ1-4GlcNAc, also have important roles in osteoclastogenesis. [14][15][16][17][18][19] Therefore, in order to clarify the potential for GlcN-mediated glycosylation modification, we investigated the effect of GlcN treatment on the pattern of glycosylation using lectin blotting of cell extracts with SSA, MAM, RCA120, PHA-E 4 , Con A, and LCA, which mainly recognize α2,6-linked sialic acid, α2,3-linked sialic acid, Galβ1-4GlcNAc, bisecting GlcNAc, high mannose type Nglycan, and N-glycan core modified with fucose, respectively (Figs. 2B-G).…”
Section: Glcn Suppresses the Osteoclastic Differentiation Of Raw264 Cmentioning
confidence: 99%